Colour effect on physiology in stimulating environment - Ab Jalil, Nurlelawati; Mohd Yunus, Rodzyah; Sheikh Said, Normahdiah; Mohamed Iqbal, Mimi Iznita (UPM Press, 2016)
Colour is an environmental stimulus that exerts an influence on human beings in a multitude of ways. The effect of colours has been abundantly unequivocally demonstrated in previous research on the integration of multimodal approaches, such as from the psychological, performance and non-performance and preferences assessments. Nevertheless, little research has been conducted locally on the integration of physiological assessment and consideration of subjects’ living ecology, this being particularly true in the field of design. The objective of this paper is to propose an optimal colour for the hostel environment of female university students based on their heart rate responses. Four determined colours, namely strong red, bluish-green, pink and white, were painted in their rooms and divided according to exposures. In the experiment, a test and re-test method of assignment was conducted. The results show that subjects in the strong red environment were stimulated after a short exposure, while subjects in the bluish- green environment were stimulated after long and sustainable periods of exposure. In summary, the significance of a coloured environment is discussed with suggestions for a short, longer and sustainable period of exposure from a physiological perspective, the aim of which being better engagement.